2008
DOI: 10.1148/radiol.2482071838
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized3He MR Imaging: Physiologic Monitoring Observations and Safety Considerations in 100 Consecutive Subjects

Abstract: Purpose:To evaluate the safety of hyperpolarized helium 3 ( 3 He) magnetic resonance (MR) imaging. Materials and Methods:Local institutional review board approval and informed consent were obtained. Physiologic monitoring data were obtained before, during, and after hyperpolarized 3 He MR imaging in 100 consecutive subjects (57 men, 43 women; mean age, 52 years Ϯ 14 [standard deviation]). The subjects inhaled 1-3 L of a gas mixture containing 300 -500 mL 3 He and 0 -2700 mL N 2 and held their breath for up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 34 publications
2
39
0
1
Order By: Relevance
“…This technique is a safe ( 14 ) and highly sensitive method with which to characterize the severity and distribution of alveolar structural abnormalities. In this approach, the lung acini are treated-in the framework proposed by Haefeli-Bleuer and Weibel ( 15 ) He diffusion measurements are used to determine values for acinar duct radii ( R ) and airway lumen radii ( r ) and to determine the depth of the alveolar sleeve ( h ) in each image pixel with the following equation: h = R 2 r .…”
Section: Subject Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique is a safe ( 14 ) and highly sensitive method with which to characterize the severity and distribution of alveolar structural abnormalities. In this approach, the lung acini are treated-in the framework proposed by Haefeli-Bleuer and Weibel ( 15 ) He diffusion measurements are used to determine values for acinar duct radii ( R ) and airway lumen radii ( r ) and to determine the depth of the alveolar sleeve ( h ) in each image pixel with the following equation: h = R 2 r .…”
Section: Subject Selectionmentioning
confidence: 99%
“…In contrast, in subjects with an FEV 1 /FVC ratio between 70% and 79%, there were signifi cant differences in acinar duct radii, alveolar depth, and mean chord length compared with subjects with an FEV 1 /FVC ratio of 80% or more, indicating that 3 He lung morphometry MR imaging is capable of depicting and transient (duration of P O 2 decrease, 48 seconds 6 10; range, 32-99 seconds). The safety fi ndings in these subjects were incorporated into a 100-subject safety study previously reported in this Journal ( 14 ). Figure 2 shows 3 He MR and CT images in three subjects; there are large abnormalities and heterogeneity in 3 He lung morphometry parameters in the subject with GOLD 0 disease who is a smoker and the subject with GOLD 2 disease who is a former smoker.…”
Section: Clinical Testingmentioning
confidence: 99%
“…Computed tomography (CT) using xenon gas measures ventilation from the gas wash-in and wash-out rate but is limited by expensive equipment and anesthetic properties of xenon gas (2). Different magnetic resonance imaging (MRI) techniques have been proposed to visualize ventilation defects, but currently, they are only partially quantitative and are able to provide low anatomic detail (3,4).…”
mentioning
confidence: 99%
“…The results can be used to calculate the average surface area and volume of individual alveoli and alveolar duct units as well as the total number of alveoli (34). Furthermore, these experiments are safe and suitable for in vivo studies in humans (15).…”
mentioning
confidence: 99%